2020
DOI: 10.1002/mds.28343
|View full text |Cite
|
Sign up to set email alerts
|

Prodromal Spinocerebellar Ataxia Type 2 Subjects Have Quantifiable Gait and Postural Sway Deficits

Abstract: Background The search for valid preclinical biomarkers of cerebellar dysfunction is a key research goal for the upcoming era of early interventional approaches in spinocerebellar ataxias. This study aims to describe novel preclinical biomarkers of subtle gait and postural sway abnormalities in prodromal spinocerebellar ataxia type 2 (pre‐SCA2). Methods Thirty pre‐SCA2 patients and their matched healthy controls underwent quantitative assessments of gait and postural sway using a wearable sensor‐based system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 40 publications
9
59
0
Order By: Relevance
“…Fallers were identified as a subject group in four studies [ 28 , 29 , 30 , 31 ]. The majority of papers investigated postural sway in neurological conditions, including Parkinson’s disease (PD) [ 32 , 33 , 34 , 35 ], multiple sclerosis (MS) [ 36 , 37 ], Huntington’s disease [ 38 ], progressive supranuclear palsy [ 33 ], muscular dystrophy [ 39 ], cerebellar ataxia [ 40 , 41 ], and a single case study of person with a stroke [ 42 ]. Only one musculoskeletal condition was investigated: anterior cruciate ligament reconstruction rehabilitation [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fallers were identified as a subject group in four studies [ 28 , 29 , 30 , 31 ]. The majority of papers investigated postural sway in neurological conditions, including Parkinson’s disease (PD) [ 32 , 33 , 34 , 35 ], multiple sclerosis (MS) [ 36 , 37 ], Huntington’s disease [ 38 ], progressive supranuclear palsy [ 33 ], muscular dystrophy [ 39 ], cerebellar ataxia [ 40 , 41 ], and a single case study of person with a stroke [ 42 ]. Only one musculoskeletal condition was investigated: anterior cruciate ligament reconstruction rehabilitation [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…No single clinical test was used consistently. Dynamic clinical measures also included walking tests (timed up and go [ 31 , 33 , 36 , 37 , 42 ], 10 m walk [ 41 ], six-minute walk test [ 34 ], 25-foot walk test [ 37 ], and jumping (dynamic postural stability index (DPSI)) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is some inconsistency in the literature, with other studies having reported pre-ataxic changes in straight walking during clinical gait assessments 43, 44 . This discrepancy might most likely be explained with early clinical gait signs already present in these study cohorts 43,44 . None of the preataxic subjects in our cohort showed any clinical gait or balance sign, as indicated by a SARA posture&gait subscore = 0 for all preataxic subjects (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…No other clinical or cognitive changes were evidenced in this one-year longitudinal study. In the prodromal phase, mutation carriers had larger variability in both gait and postural sway control [ 37 ], suggesting deterioration of the vestibulocerebellar network. Furthermore, there is a gradual worsening of speech and swallowing [ 38 ].…”
Section: Spinocerebellar Ataxia 2 Mutagenesis and Founder Effectsmentioning
confidence: 99%